Robert and James Adam, architects of the Age of Enlightenment - Kondo, Ariyuki, 1971-; ebrary, Inc. (London : Pickering & Chatto, 2012)
During the second half of the eighteenth century British architecture moved away from the dominant school of classicism in favour of a more creative freedom of expression. At the forefront of this change were architect brothers Robert and James Adam. Without rejecting established architectural tradition, the Adam brothers were modernists, free from dogmatic adherence to a particular style.Architecture has tended to be left out of the historiography of the Enlightenment. While previous studies on the Adam brothers have focused on describing their style and their inspirations, Kondo’s work places them within the context of eighteenth-century intellectual thought. Only by examining the Adams’ work in this context can the full extent of their contribution to Enlightenment development be understood.
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: Adam, Robert, -- 1728-1792; 18. století; architekti -- Skotsko -- 18. století; britská architektura -- 18. století; osvícenství -- Velká Británie; architects -- Scotland -- 18th century; British architecture -- 18th century; enlightenment -- Great Britain; monografie; e-knihy online; monographs; e-books online; Adam, James, -- 1732-1794